Metaheuristic Solution for the Routing and Wavelength Assignment (Rwa) Problem in Wavelength-Division Multiplexing (Wdm) Optical Networks [Solución Metaheurística Para el Problema de Enrutamiento (Rwa) en Redes de Ópticas de Multiplexación por División de Longitud de Onda (Wdm)] - Rodriguez-Garcia, A (Centro de Informacion Tecnologica, 2017)
The article shows the results of a new metaheuristic based on the Snake One algorithm that has been called Snake Three. It is based on the use of links until achieving maximum congestion. In this way, some order in the use of resources is achieved by leaving free the rest of the links to satisfy the incoming or future demand. The network used in the simulation is the NSFNET, of the United States, under parameterization similar to other simulations, achieving to stress the system up to 180 Erlangs. The results show improvement in the indicator utilization of the network, while the indicator probability of blocking does not show improvement. The Snake Three metaheuristic is the latest in the Snake series and has proved its effectiveness to be used in other multiplexing scenarios.